Nacho Libre [videorecording (DVD)] - Black, Jack, 1969-; Reguera, Ana de la, 1977-; Jiménez, Héctor, 1973-; Stormare, Peter (Paramount Home Entertainment, 2017)
Ignacio 'Nacho' is a cook by day in a Mexican orphanage who moonlights as a lucha libre wrestler to raise money for the orphans.